Vpliv Organizacije držav izvoznic nafte na svetovno ekonomijo - Veršnik, Igor (Vojaškošolski zbornik, 2024)
The discovery of oil sparked one of the greatest industrial revolutions in human history and fundamentally shifted the dynamics of global power. The Organization of the Petroleum Exporting Countries (OPEC) was established in 1960 with the aim of coordinating and unifying its members' oil policies to stabilize the oil markets. OPEC plays a crucial role in the global energy framework by influencing oil prices and production quotas, which significantly impacts the global economy. The organization is facing the challenges of transitioning to renewable energy sources and reducing carbon footprints. OPEC's vision is focused on the changing energy trends, ensuring energy security, and promoting cooperation and dialogue between energy producers and consumers in order to address the challenges of sustainable development together.
Keywords: global economy; green transition; Mednarodne organizacije; Mednarodni gospodarski odnosi; Mednarodni odnosi; Nafta; oil; OPEC; Regionalizem (mednarodna skupnost); svetovno gospodarstvo; zeleni prehod